Classification of Health and Nutritional Status of Toddlers Using the Naïve Bayes Classification - Saputra, Yogi; Khoirunisa, Nurfitria; Arinal Haqq, Syauqi (CoreID Journal, 2023)
Life is characterized by the presence of symptoms of growth and development. The growth and development of the degree of health of each individual are different. In this case, one of the efforts to improve health status is to improve nutritional status. Nutritional status is the state of the body related to food consumption patterns and the use of nutrients that are tailored to the body's needs. Improving nutritional status is useful for increasing body resistance and promoting normal growth. In the daily actualization of the nutritional status of toddlers at the posyandu, it is usually obtained through anthropometric measurements, namely by using the weight/age index or weight-for-age to determine nutritional status. However, in measuring with anthropometry, there was confusion in determining nutritional quality, so to get accurate results, a data mining method is needed, namely the Naive Bayes Classification (NBC) Algorithm, which will be implemented in research. With this research, it is hoped that it can help posyandu cadres in the Baros sub-district, Cimahi sub-district, and Cimahi city determine the level of health and nutritional status of toddlers better and more accurately.